Physical frailty, cognitive and functional status in institutionalized older adults - Silva, Juliana Campos Cardoso (2022)
Objective: To investigate the prevalence of frailty and its association with cognitive state and functional capacity in Brazilians institutionalized older adults. Methods: Cross-sectional study, conducted with institutionalized older adults from two Brazilian cities. Cognitive status, functional capacity and frailty were evaluated through the Mini-Mental State Examination (MMSE), KATZ index, and frailty phenotype, respectively, besides anthropometry and physical activity. Results: This study included 73 older adults with a mean age of 78.6 ±10.44 years. 63% were female, 47.9% were the very old (> 80 years) and 32.1% were underweight. The prevalence of frailty was 57.5%. It was observed that the older adults with frailty mostly had functional dependence (68.3%; p<0.01); cognitive deficit (69.0%; p<0.01); and were inactive (97.3%; p=0.01). There was an association of frailty with cognitive status (PR=1.90; CI: 1.17 - 3.06) and functional capacity (PR=2.97; CI: 1.18 - 3.11). Conclusion: The results showed high prevalence of frailty among institutionalized older adults and its association with functional incapacity and cognitive decline.